The influencing factors of tumor-related sarcopenia: a scoping review - Tian, Chun; Li, Na; Gao, Ya; Yan, Yan (BMC cancer, 2025)
Background and objective As the number of cancer cases is increasing dramatically worldwide, patients with cancer are facing serious threats of nutritional loss, sarcopenia, and even cachexia in the early stages of the disease. Sarcopenia is closely associated with poor prognosis of patients with cancer; however, there is a significant gap in the current clinical knowledge of tumor-related sarcopenia and the means to prevent and control it. The aim of this study is to explore the prevalence and influencing factors of tumor-related sarcopenia through a scoping review, and to provide guidance for future research directions and the development of intervention protocols. Methods Using computerized search methods, we extensively searched multiple authoritative databases, including CNKI, Wanfang Database, FMRS, Cochrane Library, PubMed, Embase, Web of Science, Scopus, and BMJ, with a search time limit from the establishment of the databases to July 16, 2024. Systematic data extraction, integration, and analysis were performed on the included studies, and the research results were finally summarized and reported. Results A total of 22 papers involving 20069 patients with cancer were included, and the prevalence of sarcopenia ranged from 8% to 84.96%. There were 54 influencing factors of tumor-related sarcopenia, risk factors including low BMI, advanced age, male sex, and TNM stage IV, and associated factors including NRS2002 score ≥ 3, long-term smoking history, diabetes mellitus, tumor size more than 4 cm, and lymph node metastases. Conclusion The prevalence of tumor-related sarcopenia is high and influenced by numerous factors, and most of the literature included in this review were cross-sectional and retrospective studies. Future studies urgently need to adopt a more rigorous longitudinal design in order to deeply investigate the causal relationship between factors and sarcopenia, and further exploration of factors with unclear mechanisms is needed, as well as to carry out intervention studies based on this group, in order to delay or even stop the sarcopenia development process and improve the prognostic quality of patients with cancer.